COMMUNITY FORESTRY IN BANGLADESH - A CASE STUDY OF BERAGI - POMRE COMMUNITY FORESTRY MODEL - SS., Islam (วารสารวนศาสตร์ไทย, 2022)
A case study of Betagi-Pomta Community Forestry Project was done at Chittagong district in Bangladesh. The project started functioning at Betagi with 82 settlers each alloed 1.62 ha of land in 1979 and Pomra with 152 settlers each alloted 1.62 ha of land in 1980. The main objective of the study was to extend the knowledge gained from the Betagi-Pomra experence in unproductive hilly areas to other areas in the country. A complete enumeration of the settlers at Betagi and sampling of the settlers at Pomra were carried out in both 1985 and 1994. Data on family members, land utilization, growing stock, income, expenditure, financial assistance, marketing, training, etc., were colleted in a designed questionnaire. The land expectation value was estimated to be Tk. 46000 at Betagi and Tk. 43333˙ at Pomra indicating prospective land use pattern. The input-output ratio stood at about two at Betagi and two at Pomra without considering future cost and benefit of planted stock. The internal rate of return was found to be 104 % at Betagi and 90 % at Pomra. Annual farm farm income per family in 1994 was increased to more than double both at Betagi and Pomra compared to family income in 1985. In view of the estimated characteristics, the Betagi-Pomra model porvided employment opportunities, conversion to denuded hills into green crops, ideal cropping pattern, proper market mechanism, community stability, self-sufficiency, decrease in social crimes, etc. The model may be replicated to other denuded and unproductive hilly areas in Bangladesh.